The Contributions of School Principals as Constructivist Leaders to Their Schools’ Organizational Change - YILDIRIM, M. Cevat; KAYA, Ahmet (Asian Journal of Education and Training, 2019)
The purpose of this paper is to determine the contributions of school principals as constructivist leaders in their schools’ according to teachers’ opinions. This study is qualitative research based on a phenomenological model. Researchers collected data through the semi-structured interview method. The study group was determined by a maximum variation sampling and composed of 13 teachers working in the province of Şanlıurfa, Turkey. Researchers analyzed the data using the content analysis method. The research found that school principals as constructivist leaders contributed to their schools’ organizational change. These contributions are collected under six categories: learning and teaching, sharing leadership, communication and interaction, a safe school environment, encouragement, and strategic planning. This paper makes two contributions to extant literature on this topic. Firstly, this paper facilitates the understanding of constructive leadership roles among principals. Secondly, this paper helps us determine the contributions of school principals as constructive leaders to the organizational change in their school, thus contributing to a better understanding of school leadership.